The discovery of the most UV–Ly α luminous star-forming galaxy: a young, dust- and metal-poor starburst with QSO-like luminosities. (16th September 2020) - Marques-Chaves, R; Álvarez-Márquez, J; Colina, L; Pérez-Fournon, I; Schaerer, D; Dalla Vecchia, C; Hashimoto, T; Jiménez-Ángel, C; Shu, Y
ABSTRACT: We report the discovery of BOSS-EUVLG1 at z  = 2.469, by far the most luminous, almost un-obscured star-forming galaxy known at any redshift. First classified as a QSO within the Baryon Oscillation Spectroscopic Survey, follow-up observations with the Gran Telescopio Canarias reveal that its large luminosity, M UV  ≃ −24.40 and log( L Lyα /erg s –1 ) ≃ 44.0, is due to an intense burst of star formation, and not to an active galactic nucleus or gravitational lensing. BOSS-EUVLG1 is a compact ( r eff ≃ 1.2 kpc), young (4–5 Myr) starburst with a stellar mass log( M * /M⊙ ) = 10.0 ± 0.1 and a prodigious star formation rate of ≃1000 M⊙  yr −1 . However, it is metal- and dust-poor [12 + log(O/H) = 8.13 ± 0.19, E ( B – V ) ≃ 0.07, log( L IR / L UV ) < −1.2], indicating that we are witnessing the very early phase of an intense starburst that has had no time to enrich the ISM. BOSS-EUVLG1 might represent a short-lived (<100 Myr), yet important phase of star-forming galaxies at high redshift that has been missed in previous surveys. Within a galaxy evolutionary scheme, BOSS-EUVLG1 could likely represent the very initial phases in the evolution of massive quiescent galaxies, even before the dusty star-forming phase.